The identification and neurochemical characterization of central neurons that target parasympathetic preganglionic neurons involved in the regulation of choroidal blood flow in the rat eye using pseudorabies virus, immunolabeling and conventional pathway tracing methods - Li, Chunyan; Fitzgerald, Malinda E.; Del Mar, Nobel; Cuthbertson, Sherry; LeDoux, Mark S.; Gong, Suzhen; Ryan, James P.; Reiner, Anton (Frontiers in Neuroanatomy, 2015)
The choroidal blood vessels of the eye provide the main vascular support to the outer retina. These blood vessels are under parasympathetic vasodilatory control via input from the pterygopalatine ganglion (PPG), which in turn receives its preganglionic input from the superior salivatory nucleus (SSN) of the hindbrain. The present study characterized the central neurons projecting to the SSN neurons innervating choroidal PPG neurons, using pathway tracing and immunolabeling. In the initial set of studies, minute injections of the Bartha strain of the retrograde transneuronal tracer pseudorabies virus (PRV) were made into choroid in rats in which the superior cervical ganglia had been excised (to prevent labeling of sympathetic circuitry). Diverse neuronal populations beyond the choroidal part of ipsilateral SSN showed transneuronal labeling, which notably included the parvocellular part of the paraventricular nucleus of the hypothalamus (PVN), the periaqueductal gray, the raphe magnus (RaM), the B3 region of the pons, A5, the nucleus of the solitary tract (NTS), the rostral ventrolateral medulla (RVLM), and the intermediate reticular nucleus of the medulla. The PRV+ neurons were located in the parts of these cell groups that are responsive to systemic blood pressure signals and involved in systemic blood pressure regulation by the sympathetic nervous system. In a second set of studies using PRV labeling, conventional pathway tracing, and immunolabeling, we found that PVN neurons projecting to SSN tended to be oxytocinergic and glutamatergic, RaM neurons projecting to SSN were serotonergic, and NTS neurons projecting to SSN were glutamatergic. Our results suggest that blood pressure and volume signals that drive sympathetic constriction of the systemic vasculature may also drive parasympathetic vasodilation of the choroidal vasculature, and may thereby contribute to choroidal baroregulation during low blood pressure.